Trichoscopy in alopecia areata and trichotillomania - Saurabh Sharma; Komalpreet Kaur; Jasleen Kaur; Roopam Bassi (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Background: Alopecia areata (AA) and trichotillomania (TTM) belong to non-cicatricial alopecia. These disorders may have similar clinical features with different therapeutic protocols and prognoses. Trichoscopy has proved to be an office-based tool that helps in the diagnosis and differentiation of different types of alopecia. Objective: Our objective is to differentiate and diagnose AA and TTM based on trichoscopic features. Methods: The present cross-sectional and observational study was conducted on 86 patients presenting with complaints of hair loss in the outpatient department from January 2019 to September 2020. A scalp examination was done, followed by the dermatoscopic examination with a Dermlite DL4 dermatoscope. Results: The percentage of black dots was higher in AA as compared to TTM. Broken hair at equal lengths was observed in AA, whereas broken hair at varying lengths was seen in TTM. Coiled hair, V-sign, and flame hair were only seen in TTM. Conclusion: The combination of black dots, broken hair, and exclamation mark favored the diagnosis of AA. Hair breaking at varying lengths, the V sign, flame hair, and coiled hair were exclusively seen in TTM.